Needs of Regular Teachers in Implementing the Individualized Accommodation Plans for Children with Attention Deficit Hyperactivity Discorder - Dimapilis, Annaliza S.; Gomez, Marie Grace A. (Philippine Journal of Education Studies (formerly the Education Quarterly), 2014)
The study focused on the competencies needed by teachers to implement the Individualized Accommodation Plan (IAP) for children with Attention Deficit Hyperactivity Disorder (ADHD). Data were gathered through the administration of a Focus Group Discussion (FGD) and a researcher-designed questionnaire. Participants were selected teaching personnel who have difficulties in handling students with ADHD in the inclusion program. The results of this study reveal that competencies on knowledge about Attention Deficit Hyperactivity Disorder and the Individualized Accommodation Plan and the skills to adjust in the form of accommodations, modifications and adaptations are needed by teachers. A training program on these is necessary to equip teachers with the required competencies. With these findings, it is recommended that all regular teachers undergo this kind of training to implement the IAP.
Keywords: Attention Deficit Hyperactivity Disorder, teacher competencies, individualized accommodation plan